Analisis Kadar Zat Menguap dan Kadar Karbon Terikat Pada Briket Eceng Gondok – Sekam Padi - Tauny Akbari (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Water hyacinths are aquatic weeds that have negative impacts of social, economical, and environmental. Water hyacinth has not been widely used as a renewable energy. Aim of this research is to analyze volatile matter content and fixed carbon content at renewable energy sources in the form of water hyacinth – rice husk briquette. The research design is experiment using Factorial Complete Randomized Design (3x3) with two factors; the charcoal combinations of rice husk : water hyacinth and the percentage of tapioca binder. This experiment is repeated 3 times, so there are 27 treatments. The calculation of volatile matter content using ASTMD-3175 standard and the calculation of fixed carbon content using ASTMD-3172 standard. The results show that the lowest volatile matter content (50.5%) and the highest fixed carbon content (20.3%) are owned by briquette A1P3 (combination of rice husk : water hyacinth 1:1 and the percentage of tapioca binder 5%). That briquette is not appropriate with the standards of charcoal briquette (SNI 01-6235-2000)